Sorting Sox: Diverse Roles for Sox Transcription Factors During Neural Crest and Craniofacial Development - Schock, Elizabeth N.; LaBonne, Carole (Frontiers in Physiology, 2020)
Sox transcription factors have many diverse roles during development, including regulating stem cell states, directing differentiation, and influencing the local chromatin landscape. Of the twenty vertebrate Sox factors, several play critical roles in the development the neural crest, a key vertebrate innovation, and the subsequent formation of neural crest-derived structures, including the craniofacial complex. Herein, we review the specific roles for individual Sox factors during neural crest cell formation and discuss how some factors may have been essential for the evolution of the neural crest. Additionally, we describe how Sox factors direct neural crest cell differentiation into diverse lineages such as melanocytes, glia, and cartilage and detail their involvement in the development of specific craniofacial structures. Finally, we highlight several SOXopathies associated with craniofacial phenotypes.